Optimizing Rehabilitation Strategy for Walking after Stroke： from Assisted Walking Training to Brain-Limb Cooperative Therapy - YAN Tiebin (康复学报)
Recovery of walking function after stroke is the most urgent need of patients and their families. It is also the primary goal when planning rehabilitation treatment plans with patients. For a long time, experts in the field of neurological rehabilitation have been exploring effective methods to accelerate the recovery of walking function after stroke. From various traditional Chinese medicine such as acupuncture on the limbs of patient, and modern rehabilitation technologies for paralyzed limbs (such as neurodevelopmental therapy, functional electrical stimulation, walking bicycle, and walking robot, etc.) to non-invasive brain stimulation technologies for focal brain (such as transcranial magnetic stimulation, transcranial direct current stimulation, and head acupuncture, etc.). A large number of clinical evidence-based studies have proved that these technologies are effective methods at different levels of evidence. In recent years, with the help of the 10-year research findings of brain in the 1990s, the rehabilitation for improving walking function after stroke has also been changed significantly. It began to develop from discrete target organ (such as limb or brain) to multi-target cooperative or mode therapy combining brain and limb, which gave birth to a new treatment mode: brain-limb cooperative therapy mode. Focusing on the theme of optimizing rehabilitation strategy for walking after stroke, this paper provides a brief introduction on the concept of this brain-limb cooperative treatment mode, focuses on several optimized combinations of brain-lower limb cooperative treatment modes related to improving walking function after stroke, and also a few related research papers of clinical application on this mode were published in this issue as supporting data. Through this review and the papers published in this issue, we hope to attract the attention of domestic stroke rehabilitation professionals to the brain-limb cooperative treatment model, and actively apply it in the rehabilitation treatment of improving walking function after stroke. Similar related research could be duplicated to further clarify this mode. By analogy, this brain-limb cooperative treatment model is extended to the rehabilitation treatment of upper limb function recovery after stroke, and the clinical application and research of brain-limb cooperative treatment model are expanded. From the perspective of stroke rehabilitation, the strategy of lower limb rehabilitation after stroke in the future should be to more effectively improve or restore the original walking function of patients. Therefore, the early intervention of "error free learning" rehabilitation strategy with walking as the core should implement the whole process of stroke lower limb rehabilitation. Only when the walking mode input from the periphery to the center is correct, the walking command output from the center can be correct. Brain-limb cooperative therapy is an effective guarantee for realizing this closed loop.